A retrospective study on LDL-C goal attainment in readmitted hypertriglyceridemia patients: risk factor analysis - Ji, Yuan; Chadha, Arsheen; Krity, Abhash; Huang, Shenglan (Frontiers in Endocrinology, 2025)
ObjectiveDespite positive impacts of lipid-lowering therapies (LLTs), the low-density lipoprotein cholesterol (LDL-C) target attainment remains suboptimal. This study aimed to investigate LDL-C goal achievement per the 2023 China guideline for lipid management among rehospitalized hypertriglyceridemia patients, who had higher chances to access the knowledge associated with lipid management and treatment, and evaluate the risk factors for LDL-C.MethodsThis retrospective study was performed among rehospitalized hypertriglyceridemia patients between July 2020 and May 2023. The department-specific latent class trajectory modeling was implemented to assess the longitudinal lipid profiles. The risk factors of goal attainment were evaluated using multivariate Cox regression analysis.ResultsAmong 8905 readmitted patients, 5045 (56.7%) had two admissions. Only 27.1% consistently achieved LDL-C targets, while 25% never did. Nearly half were eligible for LLTs, but only 25% received them. Continuous LLT use was associated with higher goal attainment (HR: 1.23 [95% CI: 1.12–1.36]). Most readmissions (92.15%) had increasing LDL-C trajectories and less odds of achieving the LDL goals at the last hospitalization. At the latest hospitalization, patients with higher atherosclerotic cardiovascular disease (ASCVD) risk had higher chances of achieving their LDL-C targets (hazard ratio 2.00 [95% CI, 1.70-2.36]).ConclusionsLDL-C control remains poor in this population. Continuous LLT use and ASCVD risk stratification are important factors for goal attainment, highlighting the need for better long-term management and closer monitoring of low-risk patients.